A háztartások megtakarítási szokásainak és hajlandóságának elemzése - Baranyi Aranka (2015)
My thesis work objective is to present and consider how the willingness and the opportunity of the Hungarian households' savings changed in the last period. Hungarian households and the banking sector have also preferred investments promising higher yields, but involve greater risk bearing financial instruments before the financial crisis. Due to the crisis financial products have significantly lost value, it has shaken the confidence in the financial service. One of the most significant loss touched the share Unitholders (share holders), but the investment funds are performing well nowadays. However, the yield has not returned to the pre-crisis performance after the crisis. In case of the traditional savings deposits nowadays they refer negative yields, which means that the savings structure is facing another restructuring. The state aid pension savings, investments and government securities get preferred. The introduction of the interest tax, the use of transaction fees, costs due to account management fees all point in the direction that the structure of savings will be further changed which will hopefully also leads to safe operation. Bankrupts in the circle of financial institutions have strengthen further weakening of confidence in the financial system. Hopefully, more and more strict enforcement of compliance with the prudential rules will improve in the near future and cause substantial strengthening in confidence. The population has improved propensity to save, but the size remains a concern in real incomes, after the financial crisis. The willingness is necessary but not sufficient condition to actually grow in a seed cleaning. Many households have indebted during the years before the crisis. In addition, the rise in interest rates on foreign currency loans and the depreciation of the forint significantly increased the debt burden. The gradual repayment of debt in net terms means savings. The precautionary household have accumulated savings for the past few years, built on the crisis caused negative experiences (unemployment). The aging population also strengthen the role and the need of savings, particularly in the social contribution tax paid by the employer does not form the basis for individual pension insurance, so by all means savings are necessary. The net financial assets of households have increased since 2010, it has reached historically high levels in recent years, while the gearing ratio has fallen to the level of the pre-crisis years.